Do Chinese International Students’ Personalities Change During Cross-National Transitions? - Wang, Kenneth T.; Tian, Lu; Fujiki, Mayo; Bordon, Jennifer J. (Journal of International Students, 2017)
Perfectionism is a multidimensional personality construct salient for international students; they are known to be likely high achievers in their home country and face several acculturative challenges after crossing national borders. This study examined whether perfectionist types changed during cross-national transitions in a sample of 227 Chinese international students studying in the U.S. Individuals were classified into different types of perfectionists—adaptive, maladaptive, and non- perfectionists. Results indicated that 40% of the participants’ perfectionist types changed during their cross-national transition. After studying in the United States, more non-perfectionists became perfectionists than perfectionists that turned into non-perfectionist. Acculturative stress predicted the direction of shift; nonperfectionists who perceived higher levels of acculturative stress were more likely to change into maladaptive perfectionists than adaptive perfectionists.